2021
DOI: 10.1111/jhn.12871
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dietary interventions in individuals with substance use disorders for illicit substances or illicit use of pharmaceutical substances: A systematic review

Abstract: Background: Disordered eating habits, poor dietary intake and nutritional status, and altered body composition are highly prevalent among individuals with substance use disorders. This systematic review aimed to evaluate the efficacy of dietary interventions in adults with substance use disorders for illicit substances or illicit use of pharmaceutical substances.Methods: Eight scientific databases were searched using predetermined text word and subject heading (MeSH) searches for experimental studies published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Three systematic reviews with a total of 20 dietary intervention studies in individuals with substance use disorders were included. 26,83,84 Two reviews were published in 2020 83,84 and one in 2021, 26 and all included studies with adult populations. Figure 4 depicts the search dates of the reviews.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three systematic reviews with a total of 20 dietary intervention studies in individuals with substance use disorders were included. 26,83,84 Two reviews were published in 2020 83,84 and one in 2021, 26 and all included studies with adult populations. Figure 4 depicts the search dates of the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…84 Whatnall et al focused on any nutrition intervention in adults with substance use disorders for illicit substances or illicit use of pharmaceutical substances. 26 All three reviews reported mental health outcomes for one or more included study, while only Whatnall et al and McLean et al reported dietary outcomes for one or more included studies. 26,84 The consistent conclusion across the three reviews was the lack of and/or limited range of dietary intervention studies, with Galduroz et al…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations